Using self-assessment as a formative assessment tool in an English-Chinese interpreting course: student views and perceptions of its utility. (2nd January 2020) - Han, Chao; Fan, Qin
ABSTRACT: Student self-assessment has been increasingly used as a formative assessment tool in interpreter education to help students foster learner autonomy, self-regulation and life-long learning. However, there seems to be little empirical research on how interpreting students perceive and view self-assessment. We therefore report a qualitative study, based on 38 students' reflective observations, to shed light on potential benefits and drawbacks of self-assessment which was practiced throughout a ten-week consecutive interpreting course. Inductive content analysis reveals 21 emerging themes, categorized under four general dimensions: Comments (C), Benefits (B), Drawbacks (D) and Suggestions (S). Data analysis indicates that overall self-assessment was beneficial, making students self-aware and self-reflective, but it may also have produced differential effects on different student groups (e.g., motivating some students, while demoralizing others). The study also reveals emergent themes that have not been reported in previous interpreting literature, and identifies some implementation problems that require special attention. Practical implications of the research results are discussed regarding the use of self-assessment as a formative pedagogic exercise.